The economic costs, management and regulation of biological invasions in the Nordic countries - Kourantidou, Melina; Verbrugge, Laura N.H.; Haubrock, Phillip J.; Cuthbert, Ross N.; Angulo, Elena; Ahonen, Inkeri; Cleary, Michelle; Falk-Andersson, Jannike; Granhag, Lena; Gíslason, Sindri; Kaiser, Brooks; Kosenius, Anna Kaisa; et al. (Journal of Environmental Management, 2022)
Funding Information: The authors acknowledge the French National Research Agency ( ANR-14-CE02-0021 ) and the BNP-Paribas Foundation Climate Initiative for funding the InvaCost project that allowed the construction of the InvaCost database, as well as the Norwegian Research Council's MARINFORSK project PICO ( 302114 ). The present work was conducted following a workshop funded by the AXA Research Fund Chair of Invasion Biology and is part of the AlienScenario project funded by BiodivERsA and Belmont-Forum call 2018 on biodiversity scenarios. LV received funding from the Faculty of Agriculture and Forestry of the University of Helsinki . RC is funded by a fellowship from the Leverhulme Trust ( ECF-2021-001 ). EA's contract comes from the AXA Research Fund Chair of Invasion Biology of University Paris Saclay. CD is funded by the BiodivERsA -Belmont Forum Project “Alien Scenarios” ( BMBF/PT DLR 01LC1807C ). Publisher Copyright: © 2022 A collective understanding of economic impacts and in particular of monetary costs of biological invasions is lacking for the Nordic region. This paper synthesizes findings from the literature on costs of invasions in the Nordic countries together with expert elicitation. The analysis of cost data has been made possible through the InvaCost database, a globally open repository of monetary costs that allows for the use of temporal, spatial, and taxonomic descriptors facilitating a better understanding of how costs are distributed. The total reported costs of invasive species across the Nordic countries were estimated at $8.35 billion (in 2017 US$ values) with damage costs significantly outweighing management costs. Norway incurred the highest costs ($3.23 billion), followed by Denmark ($2.20 billion), Sweden ($1.45 billion), Finland ($1.11 billion) and Iceland ($25.45 million). Costs from invasions in the Nordics appear to be largely underestimated. We conclude by highlighting such knowledge gaps, including gaps in policies and regulation stemming from expert judgment as well as ...